OX1 and OX2 orexin/hypocretin receptor pharmacogenetics - Thompson, Miles D.; Xhaard, Henri; Sakurai, Takeshi; Rainero, Innocenzo; Kukkonen, Jyrki P. (Frontiers in Neuroscience, 2014)
Orexin/hypocretin peptide mutations are rare in humans. Even though human narcolepsy is associated with orexin deficiency, this is only extremely rarely due to mutations in the gene coding prepro-orexin, the precursor for both orexin peptides. In contrast, coding and non-coding variants of the OX1 and OX2 orexin receptors have been identified in many human populations; sometimes, these have been associated with disease phenotype, although most confer a relatively low risk. In most cases, these studies have been based on a candidate gene hypothesis that predicts involvement of orexins in the relevant pathophysiological processes. In the current review, the known human OX1/HCRTR1 and OX2/HCRTR2 genetic variants/polymorphisms as well as studies concerning their involvement in disorders such as narcolepsy, excessive daytime sleepiness, cluster headache, polydipsia-hyponatremia in schizophrenia, and affective disorders are presented. In most cases, the functional cellular or pharmacological correlates of orexin variants have not been investigated  with the exception of the possible impact of an amino acid 10 Pro/Ser variant of OX2 on orexin potency  leaving conclusions on the nature of the receptor variant effects speculative. Nevertheless, we present perspectives that could shape the basis for further studies. The pharmacology and other properties of the orexin receptor variants are discussed in the context of GPCR signaling. Since orexinergic therapeutics are emerging, the impact of receptor variants on the affinity or potency of ligands deserves consideration. This perspective (pharmacogenetics) is also discussed in the review.